PERBEDAAN PENAMBAHAN KOMBINASI BACK MASSAGE PADA INTERVENSI SENAM HAMIL DALAM MENINGKATKAN KUALITAS TIDUR IBU HAMIL TRIMESTER III - Mezzi Wulandari Arenza; Ni Wayan Tianing; I Putu Adiartha Griadhi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACTSleep disturbance in the third trimester pregnant women is caused by discomfort, an increasingly largeabdominal condition, back pain, frequent urination, fetal movement, heartburn, cramps in the legs, tiredness, difficultygetting started, and physiological changes. Sleep disorders result in decreased quality of sleep. Pregnant women whohave poor sleep quality are at risk of longer labor, cesarean delivery, premature birth, and even infant mortality. The aimof this research is to know the difference of pregnant exercise combination and back massage in improving the sleepquality of third trimester pregnant women. This research use experiment method with quasi experiment approach andresearch design is pre and post test with control design. Sample are 18 people, divided into 2 groups, 9 people intreatment groups given pregnancy exercise and back massage and 9 people in control group is given only pregnantexercise. Intervention is given 8 times. Pittsburgh Sleep Quality Index (PSQI) questionnaire used for measured of sleepquality. The result of different test of unpaired group, in the treatment group got difference of average 4,556 and controlgroup got difference mean 2,333 with p=0,004 (p<0,05). These results showed that there was a significant differencebetween the treatment group and the control group in improving the sleep quality of the third trimester pregnant women.In conclusion, there are differences in the addition of back massage combination in pregnancy exercise intervention inimproving sleep quality of third trimester pregnant women.Keyword : Pregnancy Exercise, Back Massage, Sleep Quality, Third Trimester.